Reading Anxiety: An Early Affective Impediment to Children's Success in Reading. Issue 1 (1st January 2019) - Ramirez, Gerardo; Fries, Laura; Gunderson, Elizabeth; Schaeffer, Marjorie W; Maloney, Erin A.; Beilock, Sian L.; Levine, Susan C.
ABSTRACT: Learning to read is a critical but often challenging academic task for young children. In the current study, we explore the relation between children's reading affect-–particularly anxiety-–and reading achievement in the early years of reading acquisition. We hypothesized that reading anxiety would relate to reading achievement across the school year and that boys and girls might show differential patterns in the relation between reading anxiety and achievement due to the common stereotype that boys underperform in reading. A sample of first and second grade students completed measures of reading anxiety, positive reading affect, math achievement, and reading achievement in the fall and spring. Results show that reading anxiety and reading achievement share a bi-directional relation in which fall reading anxiety predicts spring reading achievement and vice versa. Furthermore, the pattern of relation between reading anxiety and achievement differs by gender: boys appear more susceptible to the reciprocal damaging effects of reading anxiety on reading achievement across the school year. Finally, reading achievement shares a stronger relation with reading anxiety than with positive reading affect, perhaps because of the phenomenon in which negative relative to positive experiences have a greater psychological impact.